6-Substituted 1, 2-benzoxathiine-2, 2-dioxides are isoform-selective inhibitors of human carbonic anhydrases IX, XII and VA. Issue 1 (6th November 2014) - Tanc, Muhammet; Carta, Fabrizio; Scozzafava, Andrea; Supuran, Claudiu T.
Abstract : A series of 6-substituted 2-benzoxathiine-2, 2-dioxides were synthesized starting from 2, 5-dihydroxybenzaldehyde, and then screened in vitro for their inhibition properties against five human carbonic anhydrase (hCA, EC 4.2.1.1) isoforms. Abstract : A series of 6-substituted 2-benzoxathiine-2, 2-dioxides were synthesized starting from 2, 5-dihydroxybenzaldehyde, and then screened in vitro for their inhibition properties against five human carbonic anhydrase (hCA, EC 4.2.1.1) isoforms. All the compounds showed excellent selectivity against the mitochondrial (hCA VA) and the tumor associated (hCA IX and XII) enzymes.